Epidemiological assessment of predictors of caries increment in 7-10- year-olds: a 2-year cohort study - Ariana Bellotto Correa Kassawara; Elaine Pereira da Silva Tagliaferro; Karine Laura Cortelazzi; Gláucia Maria Bovi Ambrosano; Andréa Videira Assaf; Marcelo de Castro Meneghim; Antonio Carlos Pereira (University of São Paulo, 2010)
OBJECTIVE: The aim of this 2-year cohort study (2003 to 2005) was to investigate how caries experience, at initial lesions (early or non-cavited lesions) and cavited stages, predicts caries increment in permanent teeth in 7-10- year-olds. MATERIAL AND METHODS: The random sample of 765 children attending public schools in the city of Piracicaba, SP, Brazil, was divided into two groups: 423 children aged 7-8 years and 342 children aged 9-10 years. All subjects were examined by a calibrated examiner, using dental mirror and ball-ended probes, after tooth brushing and air-drying in an outdoor setting, based on the World Health Organization criteria. Active caries with intact surfaces were also recorded as initial lesion (IL). Univariate analysis was used for statistical analysis (Odds Ratios and Chi-square). RESULTS: The association between the DMFT (decayed, missing and filled teeth) increment and the presence of IL was significant only for 9-10-year-old children. The children with DMFT>0 at baseline were more prone to have DMFT increment, with the highest risk for caries increment occurring in children aged 7-8 years. CONCLUSIONS: The predictors of caries increment were the presence (at baseline) of caries experience in permanent teeth for both age groups (7-8; 9-10-year-olds) and the presence of the IL (at baseline) for 9-10-year-olds.